The concept of ‘concern for one’s carelessness’ in Abai’s Words of Edification - Salkynbay, А.Б. Салқынбай (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
Sociolinguistics studies the relationship between society and language, studies psychology, character, and mentality of a person in society through language, differentiates the use of language by various social groups, systematizes the social nature of language in psychology and ethnography, and analyzes ways to influence the characteristics of language of social conditions in society, weighs and evaluates the importance of language in public life. The purpose of the article is to study the manifestations of social problems, social attitudes and social values in the language and speech discourses of Kazakh society based on the works of Abai. Within the framework of linguopsychological and linguocultural approaches, the article analyzes for the first time Abai’s statement about «to worry about your carelessness». The task of the scientific article is to reveal, analyze and systematize the general measure of life actions defined by Abai. To study the importance of a set of actions in the formation of integrity and wholeness in the life of a person. The practical significance of the results of scientific work lies in showing the national value through Abai’s conclusions, which is becoming a spiritual necessity in modern Kazakh society. The idea of “accepting and evaluating people by words”, mentioned by Abai, is currently recognized as one of the main areas of word study in world linguistics. The article defines the dynamic rating of human and related basic values, as well as their normative concepts and principles, through the prism of Abai’s wisdom. Abai’s thoughts, formed into a complex system through historical experience, have now turned into a value concept. The analysis of Abai’s words from an axiological point of view, which is a conceptual series, is of practical importance.